REWARD, PUNISHMENT DAN KINERJA KARYAWAN PADA KARYAWAN PT BANGUN BETON INDONESIA CILEGON - Nafiudin Nafiudin; Muhammad Raka Hermawan (MANAJEMEN DEWANTARA, 2019)
This study aims to determine the effect of Reward and Punisment on employee performance in the Marketing Department of PT. Build Indonesian Cilegon Concrete. Data was collected through a questionnaire method for 30 employees as respondents who worked in the Marketing Department of PT. Build Cilegon Indonesia Concrete, the sample uses saturated samples. The research method uses quantitative methods, while the data sources used are primary and secondary data. The data collection technique uses 2 methods, namely questionnaire and literature study. The test used is a test of validity, reliability, and classical assumptions, with the analysis used is multiple regression.Y '= -2,171 + 0,13 X1 + 0,93 X2+ eThe results of the analysis of getting the independent variables have a significant effect on the dependent variable. The t test is known that the Reward value is 11.949, this shows the Reward variable has a positive effect on the performance variable. The Punishment tcount value was 14,514 which showed that the Punishment variable had a positive effect on performance. F test is known that the Fcount value is 102.392, which indicates that the independent variables together affect the dependent variable. Determination coefficient analysis obtained a value of 0.884 which means that the magnitude of the relationship of the independent variable to the dependent variable is 88.4%, the remaining 11.6% is influenced by other variables not examined in this study.Kata Kunci: Performance, Punishment, Reward